The Influence Of Job Resourcefulness On Job Crafting Mediated By Work Engagement At Employees In Sheraton Hotel Surabaya Restaurant - Ekawati Putri Nur Fatimah (Universitas Mercu Buana, 2023)
This study aims to explain how the relationship between job resourcefulness towards individual crafting and collaborative crafting is mediated by work engagement. Respondents used in this study were employees of the Sheraton Surabaya Hotel & Towers restaurant, amounting of 53 respondents. This research uses a quantitative method with census sampling and uses Partial Least Square (PLS) analysis method. The test results show that job resourcefulness has a significant effect on work engagement. The effect of job resourcefulness on individual crafting and collaborative crafting has a significant effect. Then, the test results show that work engagement can mediate the relationship of job resourcefulness with individual crafting and collaborative crafting.